2012
DOI: 10.1037/a0026534
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices and perceived stress levels among psychology graduate students.

Abstract: It is well known that stress among psychology graduate students can negatively impact academic performance, clinical skills, and personal well-being. However, less is known about factors related to stress management among psychology graduate students. The current study examined self-care practices and perceived stress among psychology graduate students Four hundred eighty-eight psychology graduate students from across the United States completed an anonymous survey of self-care practices and stress. Multiple r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
161
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 80 publications
13
161
1
6
Order By: Relevance
“…Some studies have found that self-care practices are associated with lower perceived stress levels among trainees (McKinzie, Altamura, Burgoon, & Bishop, 2006;Myers et al, 2012;Chrisman, Christopher, & Lichtenstein, 2009). Despite these positive findings, training programmes usually do not have a structured component for self-care in the core curriculum (Christopher, Christopher, Dunnagan, & Schure, 2006).…”
Section: Self-care In Clinical Psychology Training Programmesmentioning
confidence: 96%
See 3 more Smart Citations
“…Some studies have found that self-care practices are associated with lower perceived stress levels among trainees (McKinzie, Altamura, Burgoon, & Bishop, 2006;Myers et al, 2012;Chrisman, Christopher, & Lichtenstein, 2009). Despite these positive findings, training programmes usually do not have a structured component for self-care in the core curriculum (Christopher, Christopher, Dunnagan, & Schure, 2006).…”
Section: Self-care In Clinical Psychology Training Programmesmentioning
confidence: 96%
“…To support the rationale of using shorter formats, Carmody and Baer (2009) found that shortened versions of MBSR were no less effective than the standard format in decreasing psychological distress. In line with recommendations for shorter interventions, suggested intervention designs have included shorter versions of MBSR or MBCT (Carmody & Baer, 2009) and brief experiential exercises as a group during clinical training (Moore, 2008), and a student-led mindfulness group (Myers et al, 2012). The content in these intervention designs can be typical of those used in mindfulness-based programmes such as MBSR or MBCT, but with a shorter duration (Moore, 2008).…”
Section: How To Develop Mindfulness In Traineesmentioning
confidence: 96%
See 2 more Smart Citations
“…The students' integration into the university life is a multidirectional process influenced by external aspects related to the academic or socioeconomic environment, but also by individual's internal factors and his/her ability to cope with new situations (Facundes & Ludermir, 2005;Myers et al, 2012).…”
Section: Theoretical Foundation and Related Literaturementioning
confidence: 99%